2013
DOI: 10.1016/j.eplepsyres.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Loss of dendritic inhibition in the hippocampus after repeated early-life hyperthermic seizures in rats

Abstract: "Loss of dendritic inhibition in the hippocampus after repeated early-life hyperthermic seizures in rats." (2013) Summary Seizures are relatively common in children and are a risk factor for subsequent temporal lobe epilepsy. To investigate whether early-life seizures themselves are detrimental to the proper function of the adult brain, we studied whether dendritic excitation and inhibition in the hippocampus of adult rats were altered after hyperthermia-induced seizures in immature rats. In particular, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Febrile convulsions also have a detrimental effect on the inhibitory circuitry, particularly at certain periods; our results showed that febrile seizures at the postnatal day of 24 (P20-P30) had long term effects, such as decrease of PPI in dentate and CA3. Other labs also found confirming results, that febrile seizures decrease inhibition in CA1 and CA3, during adulthood (Boyce, 2013). Some researchers also found decreased PPI in DG by the perforant path stimulation (Naylor, 2005).…”
Section: Loss Of Paired Pulse Inhibition In Dentate Gyrus and Ca3supporting
confidence: 59%
“…Febrile convulsions also have a detrimental effect on the inhibitory circuitry, particularly at certain periods; our results showed that febrile seizures at the postnatal day of 24 (P20-P30) had long term effects, such as decrease of PPI in dentate and CA3. Other labs also found confirming results, that febrile seizures decrease inhibition in CA1 and CA3, during adulthood (Boyce, 2013). Some researchers also found decreased PPI in DG by the perforant path stimulation (Naylor, 2005).…”
Section: Loss Of Paired Pulse Inhibition In Dentate Gyrus and Ca3supporting
confidence: 59%
“…As we have shown, inflammatory monocytes densely infiltrate the CA1 region within hours of infection in C57BL/6J mice 6 and retraction of CA1 apical dendrites is observed shortly thereafter 8 . Apical dendrite retraction results in loss of inhibitory control of the CA3-to-CA1 circuit and is a hallmark of hyperexcitability 30 . In SJL mice infected with the Daniel’s strain of TMEV there is limited inflammatory monocyte infiltration 7 and these animals do not exhibit hippocampal injury or retraction of apical dendrites 7 and do not experience seizures 31 , further suggesting a link between inflammation and hyperexcitability in this model.…”
Section: Discussionmentioning
confidence: 99%
“…41 A separate study demonstrates that early-life hyperthermic seizures lowered inhibition in the CA1 hippocampal dendrites, and suggests that the behavioral deficits are caused by a loss of CA1 apical dendritic inhibition. 42 It has also been shown that spatial memory formation by direct excitation of entorhinal to CA1 distal dendrites may be disrupted due to lowered inhibitory regulation. Repeated administration of flurothyl seizures during early development results in immature dendritic fields in pyramidal neurons within the CA1 region of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%